2018
DOI: 10.1016/j.jtcvs.2018.02.091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selective digestive decontamination without systemic antibiotics in a major heart surgery intensive care unit

Abstract: Our study shows that SDD without parenteral antibiotics can reduce the incidence of VAP in high-risk patients after major heart surgery, with no significant ecologic influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, its benefits remain controversial, and this practice is rarely used in other regions and in the United States. In one recent article investigating the effect of gut decontamination in patients undergoing cardiovascular operations, P erez-Granda and colleagues [21] concluded that gut decontamination using a digestive solution or oral paste without parenteral antibiotics could prevent ventilator-acquired pneumonia in high-risk patients, without emergence of multidrugresistant microorganisms. Gut decontamination has not been investigated in high-risk patients undergoing cardiovascular operations as a means to prevent postoperative BSI.…”
Section: Commentmentioning
confidence: 99%
“…However, its benefits remain controversial, and this practice is rarely used in other regions and in the United States. In one recent article investigating the effect of gut decontamination in patients undergoing cardiovascular operations, P erez-Granda and colleagues [21] concluded that gut decontamination using a digestive solution or oral paste without parenteral antibiotics could prevent ventilator-acquired pneumonia in high-risk patients, without emergence of multidrugresistant microorganisms. Gut decontamination has not been investigated in high-risk patients undergoing cardiovascular operations as a means to prevent postoperative BSI.…”
Section: Commentmentioning
confidence: 99%
“…Evidence supporting SOD and/or SDD as effective techniques to prevent both VAP and decrease MDR colonization pressure is indeed clearer for specific settings, i.e., of low antibiotic resistance. In addition, in light of the findings of our review, concerns regarding potential SDD-driven selection of MDR strains should be demystified [29,30]. Similar considerations can be drawn when exploring what happens when multiple decontamination regimes are jointly employed.…”
Section: Discussionmentioning
confidence: 83%
“…Not surprisingly, the most convincing conclusions can be drawn from the studies exploring the efficacy of implementing multiple strategies into structured bundles. They have thus proven how combining multiple preventive techniques can, in many cases, lower both VAP rates and MDR pathogens colonization pressure, even resulting in a decreased incidence of MDR-VAP [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The effectiveness of such bundles should be tested in well-designed trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The first reported clinical use of SDD dates back to 1983, when it was demonstrated to prevent severe infections and reduce morbidity in critically ill intensive care unit patients. 7 In the current study of Perez Granda and colleagues, 5 after a baseline period between August 2012 and August 2013, during which the VAP prevention bundle included the measures already described, with the addition of subglottic suctioning, SDD was systematically added for all cardiac surgical patients from September 2013 to January 2015.…”
mentioning
confidence: 99%